Environmental injustice and Escherichia coli in urban streams: Potential for community‐led response. (22nd March 2022) - Davis, Lacey J.; Milligan, Richard; Stauber, Christine E.; Jelks, Na'Taki Osborne; Casanova, Lisa; Ledford, Sarah H.
Abstract: Escherichia coli are fecal indicator bacteria that reach waterbodies through aging and failing infrastructure in cities. Exposure to pathogens in untreated sewage can result in gastrointestinal disease, which frequently goes unreported. In the United States, the Clean Water Act regulates point source discharges of sewage and treated wastewater, but fecal indicator bacteria remain the second leading cause of river impairment. The burden of this contamination is not equitably distributed, with Black, Indigenous, and communities of color suffering from a disproportionate burden of untreated and overflowing waste and subsequent health impacts. Regulatory failures, and even abandonment, along with the exclusion of people of color from the mainstream environmental movement, mean that new approaches are needed to help communities empower themselves to address contamination. Community‐led groups that engage residents in addressing issues within and beyond regulatory frameworks have used approaches including trash traps, riparian planting and restoration, and community‐led monitoring. Mycofiltration, or the use of fungi to filter pollutants from water, is an emerging and understudied method of remediating E . coli . The low cost of mycofilter installation and maintenance may give agency to communities that have been unduly burdened with sewage contamination to diminish harmful exposures in the near term, even as they continue working toward longer‐term regulatory fixes. Continued research is needed to fully understand how different species of mycelium work under varying hydrologic conditions, including in‐field installations, along with long‐term monitoring and community acceptance to understand the efficacy and the potential impact of this strategy. Abstract : High concentrations of Escherichia coli make urban waterbodies unsafe for human recreation, but the use of fungi (mycelium) may help remove E . coli and improve water quality, including in areas where persistent contamination is rooted in environmental injustice.